The Place and Role of Language in Society: National Language - Nazarova Dilnoza (PT. Antis International Publisher, 2024)
This article talks about the role and importance of language in the development of society. For the development of every nation, society, state, its mother tongue and its role are of great importance. The development of the language causes inter-ethnic harmony among the population, the stages of advancement in science. Today, a number of languages around the world are losing their importance and falling out of the process of communication. Several languages are being added to the ranks of dead languages. This type of events is an obstacle for the country's development stage, no country can achieve high goals without language. For example, Latin is already among the dead languages, and now the number of users of this language is limited.